7 - From an Invocation Space to a Commercial Emporium: The Evolutionary Dynamics of the Ladipo Auto Spare Parts Flea Market in Lagos, Nigeria – the 1950s to 2016 - Ekanade Olumide (Afrika Zamani, 2022)
So much has been written about the municipal polities, economy and society in Nigeria with emphasis on Lagos. However, little attention has been given to the peculiar features and dynamics of spaces within Lagos whose constitutive nature and activities have had enormous implications for organization of social existence, politics, trade and inter-ethnic relations in Nigeria, and for (in)formal economies in Africa. One enduring economic space which has emblemized the enterprise of low-end globalization in the informal economy arena in Nigeria is the Ladipo auto spare parts market in Lagos. Ladipo has transformed from an inconspicuous ritual space to a twenty-first-century mega flea market. This article tracks the developmental trajectory of Ladipo and its streets’ spare parts trade in metropolitan Lagos. It interrogates the transformation of a religious space into a market, the spread and organization of trade, the regulatory institutions and associations that have evolved and how Ladipo has become a vote bank and platform for sub-regional economic interaction. It examines the interface between trade, politics and religion. It analyzes the changes and adaptation in the ethnic composition of Mushin, factors responsible and the impact of these dynamics. It concludes that without structural adjustment there may not have been the Ladipo flea market. Without the market, it would not have become a commercial hub for the spare parts’ trade and skill specialisation which would also have diminished Igbo influence in contemporary Lagos politics. It has also helped to create a dynamic trade culture that has helped to improve livelihoods and to blur ethnic and economic boundaries among the different ethnicities that constitute the market space, thus fostering peace among the different ethnicities in Lagos and by extension, Nigeria.